Isolation and characterization of Lycium barbarum endophytic bacteria - Abdusamatov Sokhibjon; Yasenjiang Atiguli; Mamarakhimov Oybek; Kuziyev Sherali; Kudaybergenova Ulbike; Kholboeva Gulnora (BIO Web of Conferences)
In the conditions of Uzbekistan, the endophytic bacteria isolated from the plant Lycium barbarum are considered among the first studies in the country. Using standard microbiological methods, a total of 18 types of endophytic bacteria were isolated from Lycium barbarum. All endophytic bacterial isolates were tested for their ability to produce plant growth-promoting hormones. Among the isolates with the highest enzymatic activity, 8 were selected, and their effects on pathogenic fungi were studied. As a result, nearly 60% of the endophytes demonstrated varying levels of activity against Fusarium species. The findings indicate that endophytic bacteria isolated from Lycium barbarum can be used to promote plant growth and combat their pathogens.